2012
DOI: 10.4137/cmc.s8580
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Results of Percutaneous Trans-Luminal Mitral Commissurotomy in Pregnant Women with Severe Mitral Stenosis

Abstract: BackgroundValvular heart diseases and mainly rheumatic heart diseases complicate about 1% of pregnancies. During pregnancy physiological hemodynamic changes of the circulation are the main cause of mitral stenosis (MS) decompensation. Prior to introduction of percutaneous mitral balloon commissuroplasty (PTMC), surgical comissurotomy was the preferred method of treatment in patients with refractory symptoms. PTMC is an established non-surgical treatment of rheumatic mitral stenosis. The study aimed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…The mean fluoroscopy time was between 5.5 and 9 minutes in several studies, 5,[10][11][12] while in our study, it was approximately 4.5 times shorter (i.e., 97.01±38.82 sec), which is below the harmful radiation time. During catheter balloon commissurotomy, the radiation exposure to the fetus is calculated to be less than 0.2 rad with the use of abdominal and pelvic shielding.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…The mean fluoroscopy time was between 5.5 and 9 minutes in several studies, 5,[10][11][12] while in our study, it was approximately 4.5 times shorter (i.e., 97.01±38.82 sec), which is below the harmful radiation time. During catheter balloon commissurotomy, the radiation exposure to the fetus is calculated to be less than 0.2 rad with the use of abdominal and pelvic shielding.…”
Section: Discussioncontrasting
confidence: 57%
“…The rate of maternal death and major cardiac events and abortion caused by complications was also very low in other studies. 5,9,16,20 In our case series, we found 4 preterm labors, 5 pregnancies with low birth weights, 3 abortions, and 1 stillbirth due to IUGR, which appears to be acceptable in comparison with other studies. Steves et al 15 reported a 13% rate of preterm labor in their study.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations